2012
DOI: 10.1074/mcp.m111.011486
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Proteasome-inhibitor Resistant HLA Class I Peptidomes: a Study With HLA-A*68:01

Abstract: Some HLA class I molecules bind a significant fraction of their constitutive peptidomes in the presence of proteasome inhibitors. In this study, A*68:01-bound peptides, and their parental proteins, were characterized through massive mass spectrometry sequencing to refine its binding motif, including the nearly exclusive preference for C-terminal basic residues. Stable isotope tagging was used to distinguish proteasome-inhibitor sensitive and resistant ligands. The latter accounted for less than 20% of the pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
2
9
1
Order By: Relevance
“…Mass Spectrometry-Individual HPLC fractions were analyzed via MALDI-TOF MS using a 4800 Proteomics Analyzer (Applied Biosystems), as described elsewhere (27). The mass spectra were acquired in reflector positive mode at 25 kV in the m/z range of 800 -2000, using a signal-to-noise ratio (s/n) cutoff of 3, and processed using Data Explorer software, version 4.9 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass Spectrometry-Individual HPLC fractions were analyzed via MALDI-TOF MS using a 4800 Proteomics Analyzer (Applied Biosystems), as described elsewhere (27). The mass spectra were acquired in reflector positive mode at 25 kV in the m/z range of 800 -2000, using a signal-to-noise ratio (s/n) cutoff of 3, and processed using Data Explorer software, version 4.9 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Peptide sequencing was carried out with MALDI-TOF/TOF MS/MS, as described elsewhere (27). Interpretation of the MS/MS spectra was assisted by various tools.…”
Section: Methodsmentioning
confidence: 99%
“…Electrospray-Orbitrap Mass Spectrometry Analysis-Peptide sequencing by Electrospray-Orbitrap was performed exactly as described elsewhere (34) by LC-MS/MS using an Orbitrap XL mass spectrometer (Thermo Fisher, San Jose, CA) fitted with a capillary HPLC (Eksigent, Dublin, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The ubiquitylated fraction was enriched in cytosolic versus ERassociated polysomes. Intriguingly, it has been suggested that the immunopeptidome is biased against membrane proteins [61]. Increasing translation errors coordinately increased the fraction of nascent polypeptide ubiquitylation.…”
Section: Drips Slips: All In the Rdp Familymentioning
confidence: 99%